The Development of Pre-Service Teacher’s Professional Competence in Teaching English at Kendari, Southeast Sulawesi - Saputro, Ahmad Bowo; Sakhiyya, Zulfa; Mujiyanto, Januarius (English Education Journal, 2023)
Teaching English as a second language requires pre-service educators to possess a diverse skill set and adapt to evolving teaching methodologies and language acquisition theories. Therefore, it is crucial to investigate the factors that contribute to the development of pre-service English teachers' professional competence to ensure their readiness to enter the teaching profession. This study aims to investigate the factors contributing to the development of pre-service English teachers' professional competence in teaching English, addressing the lack of research in this area. More specifically, it aims to explore the challenges faced by pre-service teachers in developing their professional competence, identify areas where current teacher education programs may fall short, and provide practical recommendations for pre-service teacher training programs. This study employs a descriptive qualitative research method by involving five pre-service English teachers participating in a School Teaching Practice Program. To gather the data, this research uses a reflection section and then analyzedcategorized. The findings highlight the significance of active learning experiences, such as fieldwork and classroom practice, in fostering the development of professional competence among pre-service teachers. Additionally, the study emphasizes the need for pre-service teachers to be adequately prepared to meet the evolving needs of English language learners, especially in the context of changing teaching methodologies and advancements in educational technology.